The Influence of Financial Literacy on the Business Sustainability of SMEs in the Tourism Sector in Kintamani: Financial Inclusion as a Mediator - Rukmiyati , Ni Made Sri; Suastini, Ni Made; Safitri, Ni Wayan Noviana (Jurnal Ilmiah Akuntansi & Bisnis, 2023)
This research aims to examine the sustainability of micro, small, and medium enterprises (MSMEs) in the tourism sector of Kintamani during the pandemic, with a specific focus on the role of financial literacy as a key factor in maintaining business sustainability. The Resource-Based View (RBV) theory serves as the primary foundation for this research, depicting financial literacy as a crucial internal resource for gaining a competitive advantage and achieving business sustainability. The research method applied is quantitative with a positivism paradigm, utilizing a variance-based or component-based approach with Partial Least Squares (PLS) to test hypotheses and form a suitable model. The research population involves MSMEs in the tourism sector of Kintamani. The findings of this research affirm that financial literacy has a significant contribution to business sustainability. This achievement is further strengthened by the discovery that financial inclusion acts as a mediator in the relationship between financial literacy and business sustainability. The contribution of this research lies in enhancing the understanding of the crucial role of financial literacy in supporting business sustainability amid the pandemic conditions. Subsequent research could further develop studies on variables influencing business sustainability, thereby enriching the understanding of factors affecting business continuity.